Targeting of cholera toxin A (ctxA) gene by zinc finger nuclease: pitfalls of using gene editing tools in prokaryotes - Nafiseh Hosseini; Hossein Khanahmad; Bahram Nasr Esfahani; Mojgan Bandehpour; Laleh Shariati; Nushin Zahedi; Bahram Kazemi (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: The study was launched to use zinc finger nuclease (ZFN) technology to disrupt the cholera toxin gene (ctxA) for inhibiting CT toxin production in Vibrio cholera (V. cholera). Experimental approach: An engineered ZFN was designed to target the catalytic site of the ctxA gene. The coding sequence of ZFN was cloned to pKD46, pTZ57R T/A vector, and E2-crimson plasmid and transformed to Escherichia coli (E. coli) Top10 andV. cholera. The efficiency of ZFN was evaluated by colony counting. Findings/Results: No expression was observed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and western blotting in transformed E. coli. The ctxA gene sequencing did not show any mutation. Polymerase chain reaction on pKD46-ZFN plasmid had negative results. Transformation of E. coli Top10 with T/A vectors containing whole ZFN sequence led to 7 colonies all of which contained bacteria with self-ligated vector. Transformation with left array ZFN led to 24 colonies of which 6 contained bacteria with self-ligated vector and 18 of them contained bacteria with vector/left array. Transformation of V. cholera with E2-crimson vectors containing whole ZFN did not produce any colonies. Transformation with left array vectors led to 17 colonies containing bacteria with vector/left array. Left array protein band was captured using western blot assay. Conclusions and implications: ZFN might have off target on bacterial genome causing lethal double-strand DNA break due to lack of non-homologous end joining (NHEJ) mechanism. It is recommended to develop ZFNs against bacterial genes, engineered packaging host with NHEJ repair system is essential.